Audit and assurance essentials for professional accountancy exams - Bagshaw, Katharine (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
This accessible beginners guide to audit and assurance begins with the fundamentals and expands to cover the details in a more measured way. Using practical examples, it breaks down the often difficult and challenging field of professional accounting.
1. Auditors, audits and other types of assurance and passing the exam first time -- 2. Taking on professional work and maintaining standards -- 3. Housekeeping : planning, materiality and documentation -- 4. The core of the audit -- 5. Corporate governance, professional liability, regulation and other current issues -- 6. Audit reporting -- 7. Fraud, money laundering, forensic accounting, financial instruments -- 8. The wider framework : assurance, other engagements, audit quality and quality control -- 9. Smaller entity audits, reviews, compilations, agreed-upon procedures engagements, not-for-profit engagements -- 10. Other assurance engagements.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Auditing -- Examinations, questions, etc; Accounting -- Examinations, questions, etc; Accounting -- Examinations, questions, etc; Auditing -- Examinations, questions, etc; BUSINESS & ECONOMICS -- Auditing; Accounting; Auditing; Electronic books; Examinations; Electronic books